Mixed Ligand Complexes of Praseodymium(III) with 8-Quinolinol and 1,10-Phenanthroline or 2,2´ -Bipyridyl into Molten Naphthalene - Mittal, V.P.; Vyas, P.C. (Asian Journal of Chemistry, 2010)
The solid-liquid extraction of mixed ligand complexes of praseodymium(III) with 8-quinolinol and 1,10-phenanthroline or 2,2-bipyridyl has been investigated in molten naphthalene-DMF. Traces of metal extracted are determined spectrophotometrically. The extraction of the mixed ligand complexes has been discussed in terms of various parameters, like Beer's law, range of concentration, molar absorptivity and Sandell's sensitivity. The results are compared with the equilibrium extraction behaviour of praseodymium(III) complexed with 8-quinolinol alone. An enhancement in extractability of praseodymium(III) due to the formation of mixed ligand complexes has been noticed.